Designing An Integrated Local Content Commodity Catalog and Monitoring Mechanism for Procurement at PT Bumi Energi - Ade Febriyani; Yuanita Handayati (Inkubis : Jurnal Ekonomi dan Bisnis, 2026)
Background: The Domestic Component Level Policy (TKDN) is a strategic instrument of the government in encouraging national industrial independence through procurement mechanisms, especially in State-Owned Enterprises (SOEs). PT Bumi Energi as a national energy company is required to integrate TKDN in every procurement process. However, its implementation still faces challenges, especially at the stage of analyzing the minimum value of TKDN and monitoring post-contract realization. Objective: This study aims to analyze the influence of the weaknesses of TKDN monitoring on the effectiveness of the procurement process at PT Bumi Energi and formulate a strategy to improve it. Methods: The research method uses a qualitative approach with a case study design. Data was collected through semi-structured interviews, participatory observations, internal document review, and benchmarking with oil and gas sector companies that have more mature TKDN practices. The analysis was carried out using thematic analysis and gap analysis to compare existing conditions with ideal conditions based on regulations and best practices. Results: The results show that the weakness of verification standards, reliance on vendor self-declaration, and the absence of an integrated TKDN database affect the effectiveness of procurement decision-making and increase governance risks. Conclusion: This study concludes that strengthening TKDN monitoring procedures, establishing clear PIC mandates, and developing an integrated TKDN commodity catalog and database system are the key strategies to enhance procurement governance effectiveness at PT Bumi Energi. These findings contribute to the micro-organizational governance literature and provide actionable policy recommendations for SOEs facing similar TKDN compliance challenges.